2021
DOI: 10.1002/ppp3.10202
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny reveals non‐random medicinal plant organ selection by local people in Benin

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 107 publications
0
27
0
2
Order By: Relevance
“…Instead, large plant families contain more medicinal plants than expected, thus supporting the non-random selection hypothesis of medicinal plants. Such positive relationship has been reported in numerous studies across different continents (Asia [ 18 ], South America [ 19 , 20 ], and North America [ 6 , 17 , 37 , 50 ], including in the Pacific [ 10 ], and in Africa [ 2 , 4 ]. Our results, using the southern African flora, provide additional support to the hypothesis, and we therefore suggest that the non-random hypothesis could perhaps be regarded as a generalizable pattern in ethnobotany.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Instead, large plant families contain more medicinal plants than expected, thus supporting the non-random selection hypothesis of medicinal plants. Such positive relationship has been reported in numerous studies across different continents (Asia [ 18 ], South America [ 19 , 20 ], and North America [ 6 , 17 , 37 , 50 ], including in the Pacific [ 10 ], and in Africa [ 2 , 4 ]. Our results, using the southern African flora, provide additional support to the hypothesis, and we therefore suggest that the non-random hypothesis could perhaps be regarded as a generalizable pattern in ethnobotany.…”
Section: Discussionmentioning
confidence: 54%
“…Several alternative hypotheses have been formulated to explain the patterns of plant use by local people (see review in [ 1 ]). However, existing studies examined these hypotheses individually [ 2 4 ], and this limits our broad understanding of how multiple drivers shape local people’s plant knowledge and use [ 5 ]. In the present study, we tested three interlinked hypotheses to explain the integration of alien plants into local medicinal flora: non-random selection, diversification, and versatility hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…From a phylogenetic perspective, this is an indication of non-random selection of alien plants. However, taxonomic non-random plant selection was initially suggested almost four decades ago to explain human-plant interactions, particularly for native plants used in traditional medicine [6,41,42]. This was later supported in several other studies, but mostly for native plants used in traditional medicine [8,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…; [1][2][3][4][5]). The selection and use of plants by humans have been shown to be non-random, but this nonrandomness has been widely demonstrated for native plants (e.g., [6][7][8][9][10]). However, it is increasingly shown that alien species intentionally selected and introduced into new environments for human use (e.g., medicine) are also non-random selections from local floras (e.g., [11]; see [12] for further references).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of authors are calling for the vast wealth of ethnobotanical knowledge documented over centuries to be used to test hypotheses and theories or to formulate new ones [3][4][5][6][7][8][9][10][11][12][13], a common practice in any scientific discipline. Some authors even questioned whether ethnobotany, as a scientific discipline, has a unifying theory, since the discipline remains, for too long, largely descriptive without clearly defined theoretical frameworks [13][14][15][16]. Consequently, there has been repeated calls for a para-digm shift towards more theory-inspired or hypothesis-driven research in ethnobotany [12].…”
Section: Introductionmentioning
confidence: 99%